THE ROLE OF VALIDATION EXPERT IN IMPROVING THE QUALITY OF MATERIAL, LANGUAGE AND VISUALS IN THE DEVELOPMENT OF HYBRID LEARNING GUIDES-BASED ON OBS APPLICATION - Erna Retna Safitri; Makmum Raharjo; Ardi Saputra; Freshy Loisan Pandesha; Nur Islamia (PEDAGOGIA, 2022)
With the Covid-19 Pandemic, the teacher's role is not only as a teacher in a formal school. This research generally aims to develop teaching materials in Hybrid learning by using video recording and streaming with the Open Broadcaster Software (OBS) application. This research uses research and development procedures or research and development. The research model used in this study is the ADDIE development model. This model has five research stages: Analysis, Design, Development, Implementation, and Evaluation. The results showed that the teaching materials developed in the Hybrid Learning method through Video Recording and streaming assisted by the Open Broadcaster Software (OBS) application were quite good. The results of expert judgments carried out by material experts, media experts, and linguists showed that the average score for the material aspect was 3.9; the media validation score was 3.9, and the language aspect validation score was 3.45. The results of this study indicate that the teaching materials developed in the Hybrid Learning method through Video Recording and streaming assisted by the Open Broadcaster Software (OBS) application are suitable for learning.